Multimodality management of sinonasal teratocarcinosarcoma in a 76‐year‐old Alaska Native female during the COVID‐19 pandemic. Issue 3 (26th March 2022) - Adams, Dara R.; Ramirez‐Garcia, Richard; Ginat, Daniel T.; Agrawal, Nishant; Seible, Dan; Cipriani, Nicole A.; Horowitz, Peleg; Pinto, Jayant M.; Chiu, Brandon L.
Abstract: Sinonasal teratocarcinosarcoma is a rare, highly aggressive tumor of the anterior skull base composed of malignant epithelial, mesenchymal, and neural tissue. Examination of cases in patients in minority populations is important in order to better understand the behavior of this neoplasm and outcomes of treatment in our nation's diverse population. Abstract : Sinonasal teratocarcinosarcoma is a rare, highly aggressive tumor of the anterior skull base composed of malignant epithelial, mesenchymal, and neural tissue. Examination of cases in patients in minority populations is important.